Penentuan Rute Distribusi Suku Cadang Kendaraan Bermotor dalam Meminimalkan Biaya Transportasi (Studi Kasus: PT. Inti Polymetal Karawang) - Ade Momon; Damara Widi Ardiatma (Universitas Bunda Mulia, 2018)
The goal of the distribution system is to deliver the product promptly, quickly and generate the minimum cost. Therefore, the development of distribution system is very important because it can support the growth and development of the company. This study aims to get the route of delivery of the most appropriate and optimal products and get transportation cost savings. PT. IPM is a company engaged in the production of automotive. The problems faced by PT. IPM is the absence of good product distribution planning and scheduling distribution process is considered not maximal. This is due to the number of routes are too many, the distance is too far delivery, the limited means of conveyance and utilization of transport space less than the maximum and the high cost of transportation. To solve the problem of PT. IPM then needed the best method, that is Saving Matrix method which is used to determine product distribution route to the customer based on the capacity of conveyance used and Nearest Neighbors method for route ordering. From the result of mathematical calculation with Saving Matrix method and algorithm with Nearest Neighbors method obtained 49 best routes for PT. IPM. The distance to be taken is as far as 6,010 kilometers with transportation cost of Rp. 46,630,527. The resulting distance saving is 22% (1,690.9 km), while the transportation cost savings that occur is 38% or Rp. 28,494,021.